Manajemen Sumber Daya Manusia dalam Lembaga Pendidikan - Zenita Dwi Tiara; Didit Supriyadi; Nelly Martini (Universitas Batanghari, 2023)
Education is a source of progress for a nation, because through education the quality of human resources in a nation can be improved. The demand to improve the quality of education in fact requires educational human resources and other human resources in order to work more optimally. Human resource management education has an important role to improve the quality of education, one of which is the development and improvement of the competence of teachers and principals. Human resource management is a human resource development that has the aim of planning, implementing, recruiting, training, and developing careers for employees or employees as well as initiatives in organizational development within an organization or a company. Human resource management is basically a way or method of managing human resources to support the achievement of organizational goals. There are five HR domains that are considered important in the development of human resources in education, namely professionalism, competitive power, functional competence, participatory excellence and cooperation.